The Effectiveness of Problem-Based Learning Model and Role Playing Assisted by Audio-Visual Media in Learning Outcomes of Social Studies at Fifth-grade Elementary School - Dwi Putra, Indrajaya; Endang Susilowati, Sri Mulyani; Purwanto, Edy (Journal of Primary Education, 2021)
Social learning is necessary in daily life to meet human needs through identifiable problem solving. However, what happened was students did not have learning experience that connects the theories with real life, learning was focused on giving materials to the students. This study aims to determine the effectiveness of problem-based learning (PBL) model and role playing assisted by audio-visual media in learning outcomes of social studies at fifth grade state elementary school Sulang 2. The research method was used a quasi- experimental design with a non-equivalent group design. The sample for experiment 1 was thought by usingPBL model assisted by audio-visual media, while the sample for experiment 2 was used role playing assisted by audio-visual media. Data analysis was performed by using kolmogorov-smirnov test with SPSS 23 aids. The mean score of post-tests in experiment class 1 increased with 77.4 point and experiment 2 with 68.4 point. The results of the t-test analysis were homogeneous, with sig value = 0.130, so that p> 0.05, so as Ho was rejected, and Ha was accepted. The results showed that 21 students in the experiment 1 and 14 students in the experiment 2 reached minimum completeness criteriaat social science in the fifth grade by 75. The results of the N-gain analysis for the experimental class 1 showed a result of 0.965 and the experimental class 2 of 0.525. Based on these findings, it was shown that learning in the experimental class 1 which experience PBL assisted by audio-visual media was more effective and could improve learning outcomes than that of the experimental class 2 which experience role playing assisted by audio-visual media.